2013
DOI: 10.1038/nature12570
|View full text |Cite
|
Sign up to set email alerts
|

Olivine crystals align during diffusion creep of Earth’s upper mantle

Abstract: The crystallographic preferred orientation (CPO) of olivine produced during dislocation creep is considered to be the primary cause of elastic anisotropy in Earth's upper mantle and is often used to determine the direction of mantle flow. A fundamental question remains, however, as to whether the alignment of olivine crystals is uniquely produced by dislocation creep. Here we report the development of CPO in iron-free olivine (that is, forsterite) during diffusion creep; the intensity and pattern of CPO depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
194
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(217 citation statements)
references
References 42 publications
20
194
3
Order By: Relevance
“…Recrystalization could further reduce the anisotropy. These mechanisms are generally not thought to affect the anisotropic patterns, although recent experiments suggest CPO from diffusion creep in olivine is possible (Miyazaki et al 2013). Both the overestimation of anisotropic strength in our models and the underestimation in observations are additional arguments for the anisotropy in the pPv B model to be unrealistically weak.…”
Section: Limitations Of These Modelsmentioning
confidence: 65%
“…Recrystalization could further reduce the anisotropy. These mechanisms are generally not thought to affect the anisotropic patterns, although recent experiments suggest CPO from diffusion creep in olivine is possible (Miyazaki et al 2013). Both the overestimation of anisotropic strength in our models and the underestimation in observations are additional arguments for the anisotropy in the pPv B model to be unrealistically weak.…”
Section: Limitations Of These Modelsmentioning
confidence: 65%
“…linear-viscous (newtonian) creep has also been experimentally observed in anorthite and forsterite aggregates (Gómez Barreiro et al, 2007;Miyazaki et al, 2013); the mechanism responsible for such LPO formation, likely 'diffusion related' although still unclear, is not accounted for in the present model. Along the same line, diffusion creep in two phase aggregates shows some quite odd behaviors, as predicted by early modeling (Wheeler, 1992) and recently observed in experimentally deformed harzburgite (Sundberg and Cooper, 2008); such behaviors cannot be described in the framework of the present modeling.…”
Section: Specifics Of the Present Second-order (So) Modelmentioning
confidence: 79%
“…It has also been suggested that a distinct LPO may form in olivine when it is deformed via diffusion creep (Miyazaki et al 2013). Similarly, a transition to a grain boundary sliding deformation mechanism may explain the presence of the B-type deformation fabric, rather than water-induced changes to the relative strengths of olivine slip systems.…”
Section: Discussionmentioning
confidence: 99%